Analisis Kualitas Garam Tradisional Di Desa Mausamang Kecamatan Alor Timur - Zakarias Adrianto Mautuka; Rambu Yorinata Banik; Martasiana Karbeka (Peneliti.net, 2023)
This study aims to determine the quality of traditional salt in Mausamang Village based on the percentage of water content, NaCl content, KIO3 and Pb levels compared to the standard according to SNI 01-3556-2010. Sampling was carried out at the location of the salt desert in Mausamang Village. The method used in this research is the gravimetric method to determine the water content and the titration method to determine the levels of NaCl and iodine, while the atomic absorption spectrophotometer (AAS) is used to analyze lead (Pb), in the traditional salt of Mausamang Village. The results showed that at 4.51% water content, 5.85% NaCl content, negative KIO3 content and 0.0006024 mg/g Pb metal compared to the standard standard, salt from Mausamang Village did not meet the requirements for consumption.